Study on the Path of Civic and Political Education in Promoting the Formation of College Students' Outlook on Life and Values and the Enhancement of Psychological Quality (Lex localis - Journal of Local Self-Government, 2025)
In the current era of complicated information, the construction of three views and the cultivation of psychological quality of young college students are subject to many challenges. This paper tries to promote the cultivation of good outlook on life and values and excellent psychological quality among college students through the means of Civic and Political education. The study proposes a path of Civic Education to guide college students' outlook on life and values, and combines it with the path of Civic and Psychological Parenting. Through empirical research, the role of the Civic and Political Education Path proposed in this paper in the formation of college students' outlook on life and values and the improvement of psychological quality is examined. Before the experiment, the experimental group and the control group belonged to the same level in outlook on life values and psychological quality. After the experiment, the experimental group's outlook on life values and psychological quality were significantly improved, and the scores of both outlook on life values and psychological quality were much higher than those of the control group. The outlook on life values and psychological quality of the experimental group were significantly improved after the experiment, while the control group did not show significant changes. The path of civic education proposed in this paper plays a positive role in the formation of outlook on life values and psychological quality of college students.